Microstimulation of afferents in the sacral dorsal root ganglia can evoke reflex bladder activity. Issue 1 (24th January 2014) - Bruns, Tim M.; Weber, Douglas J.; Gaunt, Robert A.
Abstract Aims Pudendal afferent fibers can be excited using electrical stimulation to evoke reflex bladder activity. While this approach shows promise for restoring bladder function, stimulation of desired pathways, and integration of afferent signals for sensory feedback remains challenging. At sacral dorsal root ganglia (DRG), the convergence of pelvic and pudendal afferent fibers provides a unique location for access to lower urinary tract neurons. Our goal in this study was to demonstrate the potential of microstimulation in sacral DRG for evoking reflex bladder responses. Methods Penetrating microelectrode arrays were inserted in the left S1 and S2 DRG of six anesthetized adult male cats. While the bladder volume was held at a level below the leak volume, single and multiple channel stimulation was performed using various stimulation patterns. Results Reflex bladder excitation was observed in five cats, for stimulation in either S1 or S2 DRG at 1 Hz and 30–33 Hz with a pulse amplitude of 10–50 µA. Bladder relaxation was observed during a few trials. Adjacent electrodes frequently elicited very different responses. Conclusions These results demonstrate the potential of low‐current microstimulation to recruit reflexive bladder responses. An approach such as this could be integrated with DRG recordings of bladder afferents to provide a closed‐loop bladder neuroprosthesis. Neurourol. Urodynam. 34:65–71, 2015. © 2014 Wiley Periodicals, Inc.